On the Concepts of narečje and diasystem in Serbian and Croatian Dialectology and Standard Language Scholarship - Vukotić, Vuk (Slavistica Vilnensis, 2022)
The aim of this paper is to present a historical analysis of the concept of narečje (narječje) and diasystem in dialectology since their beginnings on the territory of contemporary Croatia and Serbia until today. These concepts are normally used to denote a dialectological unit higher than a single dialect, and also play an important role when defining standard languages. Regardless of their uniqueness and importance, there is no historical overview of their development. The historical analysis identified two distinct periods: (1) the comparative-descriptive and (2) the neogrammarian-structuralist. The first is ascribed to Vuk Karadžić and the philological school, who understood narečje as contemporary linguistic forms, while the second was started by Aleksandar Belić, who understood them primarily as homogenous proto-dialects, which split into smaller dialects over time. This understanding of narečje remained dominant even during the times Pavle Ivić introduced structural dialectology, as well as in the research of Dalibor Brozović, who introduced the alternative notion of diasystem in the 1970s. The conclusions invite for a revision of the concept of a narečje and diasystem in dialectology and the studies of standard languages. On a practical level, the author suggests that for contemporary varieties, adjectival forms or forms clearly refering to a hypothetical origin should be used (i.e. Štokavian dialects or dialect of Štokavian origin), while narečje, or noun-forms (i.e. Štokavian narečje, Štokavica, Štokavština) should either be avoided or substituted with reconstructed proto-dialect.
Keywords: narečje / narječje; diasystem; protodialect; neogrammarian school; Serbian dialectology; Croatian dialectology